2010
DOI: 10.4314/wajm.v29i1.56183
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mortality and Perinatal Risk Factors in Rural Southwestern Nigeria: A Community-Based Prospective Study

Abstract: BACKGROUND: Reliable data on births and deaths particularly at the community level are scarce yet they are urgently needed to inform policy and assess the improvements which may have occurred with recent interventions. OBJECTIVE: To determine neonatal mortality rate and identify perinatal risk factors associated with neonatal deaths. METHODS: In a community-based prospective study, baseline data on births and deaths were collected as they occurred in a rural community of Southwest Nigeria from 1993 to 1998. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…Like other studies, neonates appeared at highest risk from infection in the first week of life (Lawn et al. 2006; Lawoyin et al. 2010).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Like other studies, neonates appeared at highest risk from infection in the first week of life (Lawn et al. 2006; Lawoyin et al. 2010).…”
Section: Discussionsupporting
confidence: 57%
“…2008). Prior research has shown links between home delivery and poor birth outcomes (Lawoyin et al. 2010), because of obstetric complications and infection.…”
Section: Discussionmentioning
confidence: 99%
“…The persistently high rates of maternal mortality in Nigeria are even more stark when the rates are disaggregated by political zone [2], [3]. Estimates from several studies were collated and are presented in Table 2, to illustrate variations in the picture of mortality patterns in the country [4], [5], [6], [7], [8], [9], [10]. For example, the rate is 1049 per 100,000 live births in Zamfara State [8] and 1500/100,000 live births in Sokoto State [7].…”
Section: Introductionmentioning
confidence: 99%
“…Globally and locally, studies have identified delivery assistance as a vitally important factor associated with positive improvements in maternal mortality rates [9], [10], [11], [12], [13]. Based on the analysis of MMR in 181 countries, Hogan and Foreman concluded that between 1990 and 2008, the increase in the proportion of women who gave birth with a skilled attendant was a main explanatory factor in the decline in global MMR.…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight is defined as birth weight less than 2500 g irrespective of gestational age. [1] It occurs worldwide but by far more commonly in developing countries [2] It often results from prematurity or intrauterine growth restriction [3][4] though more from the latter than the former in developing countries [5] About one quarter of newborns in developing countries start life with impaired growth in utero often resulting in LBW at delivery [6][7][8] Complications arising from this include infections, hypoglycemia, hypothermia, jaundice and perinatal asphyxia often resulting in significant perinatal mortality [2] LBW infants are also predisposed to developing neurological problems including poor attention span and have much higher burden of disease throughout life [7] They often remain undernourished throughout childhood and adolescence and easily grow into undernourished women of childbearing age who themselves deliver LBW babies [8] It is easier and better to prevent the delivery of a LBW baby than preventing the perinatal morbidity and mortality, developmental problems, failure to thrive and other life time complications consequent on its delivery.…”
Section: Introductionmentioning
confidence: 99%